Buckling Analysis of Sandwich Plate Systems with Stiffening Ribs: Theoretical, Numerical, and Experimental Approaches - Guangping Zou; Yuyang Wang; Qichao Xue; Chunwei Zhang (Advances in Civil Engineering)
This paper discusses a global buckling analysis approach for sandwich plates with stiffening ribs. The approach is based on theoretical study and is implemented by the finite element method (FEM). The equilibrium equation corresponding to critical global buckling of the sandwich plate with stiffening ribs under simple supported boundary condition is established by the energy method. The critical buckling solutions for a typical rectangular sandwich plate system (SPS) with a single stiffening rib in the longitudinal direction are then investigated while varying the potential influencing factors. The shear rigidity within the inner core exerts little effect on global buckling and can be neglected. An FEM study on elastic buckling was then conducted via ANSYS software. The advantages of the SPS were highlighted via its elastic eigenvalue buckling numerical analysis with multiple stiffeners. The ultimate buckling loads were computed similarly for different influential factors. Finally, an SPS specimen was tested in a compression test. The results showed that when the rib spacing is large, the local buckling of the plates in the grillage is controllable and the SPS is more resistant to both local and global buckling. The results based on our theoretical method agreed well with those of the FEM and experimental results.